PENGUNGKAPAN, ASIMETRI INFORMASI, DAN COST OF CAPITAL - KHOMSIYAH KHOMSIYAH; SUSANTI SUSANTI (Jurnal Bisnis dan Akuntansi, 2003)
This study examines the relationship between disclosure, asymmetry information and cost of capital. Previous researches indicate that fuller disclosure will reduce information asymmetry, and this reduces cost of capital. This study tries to test the effect of disclosure level on reducing of information asymmetry and cost of capital. Further, the research investigates both of direct and indirect effect of disclosure on cost of capital. The samples of this study cover about 73 companies listed at the Jakarta Stock exchange in 2002. Simple regression was employed to test the relationship between disclosure, information asymmetry, and cost of capital partially. The first result of this studies show that there is no relationship between disclosure and information asymmetry. Second result provides support the hypothesis that there is a positive relationship between asymmetry information and cost of capital, during the event window time. Using path analysis, the result of this study indicates that disclosure has a negative direct effect on cost of capital. But the magnitude of the total effect decreases through theinformation asymmetry.